Optimization study of ultrasound-assisted polyphenol extraction from cocoa powder and utilization of its grounds using papain solution. - Noor Ariefandie Febrianto; Teguh Wahyudi (Indonesian Coffee and Cocoa Research Institute, 2016)
Cocoa powder is one of the main products of the cocoa grinding process which is frequently used in confectionery industries. Today, the utilization of cocoa powder has been derivatized not only it can be used as food ingredient, but also expanding in its utilization in pharmaceutical. The utilization of cocoa powder mainly due to its advantageous and healthy polyphenol content which should be extracted from cocoa powder. Generally, this process will result in significant amounts of underutilized cocoa powder grounds. This research was carried out to evaluate the utilization of ultrasound-assisted extraction method to extract antioxidative compound from cocoa powder and to study the possibility of utilizing its grounds for its antioxidative compound by the use of papain solution system. The extraction study was carried out using different concentration of ethanol ranged from 53.79, 60, 75, 90 and 96.21% for 23.39, 30, 45, 60 and 66.21 min extraction time. The evaluation was carried out using the analysis of total phenolic content and DPPH radical scavenging activity. Further, freshly prepared papain was used in different concentration ranged from 2, 4 and 6% to incubate the cocoa grounds for 2, 3, and 4 hours. The obtained cocoa hydrolysate solution was then analyzed for its protein content and its antioxidant activity. The optimization study of the process was carried out using response surface methodology. This study shows that the use of 60% ethanol for 30 min extraction was optimum to extract the phenolic compound from cocoa powder. On the other hand, the use of papain revealed that the underutilized cocoa grounds could be potentially used as the source of protein and antioxidant.